Identification of novel genetic variants, including PIM1 and LINC01491, with ICD-10 based diagnosis of pulmonary arterial hypertension in the UK Biobank cohort - Pu, Alex; Ramani, Gautam; Chen, Yi-Ju; Perry, James A.; Hong, Charles C. (Frontiers in Drug Discovery, 2023)
Pulmonary arterial hypertension (PAH) is characterized by remodeling and narrowing of the pulmonary vasculature which results in elevations of pulmonary arterial pressures. Here, we conducted a genome-wide association study (GWAS) using the UK Biobank, analyzing the genomes of 493 individuals diagnosed with primary pulmonary hypertension, based on ICD-10 coding, compared to 24,650 age, sex, and ancestry-matched controls in a 1:50 case-control design. Genetic variants were analyzed by Plink’s firth logistic regression and assessed for association with primary pulmonary hypertension. We identified three linked variants in the PIM1 gene, which encodes a protooncogene that has been garnering interest as a potential therapeutic target for PAH, that were associated with PAH with genome wide significance, one (rs192449585) of which lies in the promoter region of the gene. We also identified 15 linked variants in the LINC01491 gene. These results provide genetic evidence supporting the role of PIM1 inhibitors as a potential therapeutic option for PAH.